Pengaruh Kinerja Guru Dan Motivasi Belajar Terhadap Hasil Belajar Pendidikan Agama Islam Peserta Didik Pada Smait Wahdah Islamiyah Makassar - Ibrahim, Misykat Malik; Ismail, Ilyas; Yusuf, Abd Razak (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2019)
The type of this research is ex post facto research with an associative quantitative approach. The purpose of this study was to (1) describe the performance of Islamic education teachers at SMAIT Wahdah Islamiyah Makassar, (2) describe students’ motivation to learn islamic education, (3) describe the learning outcomes of Islamic education students, (4) test the effect of teachers’ performance on the students’ learning outcomes of Islamic education, (5) examine the effect of the students’ motivation on learning outcomes of Islamic education, (6) examine the effect of teacher performance and motivation on the students’ learning outcomes of Islamic education. The population in this study were all students of class XI Semester I SMAIT Wahdah Islamiyah Makassar Academic Year 2018/2019. The result of the study reveal that; (1) the performance of Islamic education teachers at SMAIT Wahdah Islamiyah Makassar is in high category; (2) students’ motivation to learn islamic education is in high category; (3) the learning outcomes of Islamic education students, is in high category; (4) there is positive the effect of teachers’ performance on the students’ learning outcomes of Islamic education by 0,224; (5) there is positive the effect of the students’ motivation on learning outcomes of Islamic education by 0,550; dan (6) there is positive the effect of teacher performance and motivation on the students’ learning outcomes of Islamic education. by 0,554. The multiple regression model to predict the student’ learning achievement in Islamic education subject which influence by theacher’s performance and learning motivation is = 69,645 + 0,023X1+ 0,145X2. Keywords: Teacher Performance, Learning Motivation, Learning Outcomes